Efficacy and tolerability of 12-weeks treatment with lipanthyl supra or trichol in Indonesian patients with dyslipidemia (Medical Journal of Indonesia, 2007)
The relation of dyslipidemia with the development and progression of atherosclerosis and coronary artery diseases has been demonstrated.This study compared the lipid modifying effects of locally-manufactured fenofibrate (trichol) versus lipanthyl supra in a randomized double-blind controlled study.A total of sixty-eight patients with levels of HDL cholesterol≤40 mg/dL; triglyceride of 200–600 mg/dL; or LDL of ≥130 mg/dL were recruited to this study and were randomized to either receive trichol 300 mg once daily or lipanthyl 160 mg once daily. Sixty one patients completed the study. Lipid levels before and 4, 8, and 12 weeks after the treatments were measured and analyzed.Compared to baseline values, 12-weeks treatment with either lipanthyl or trichol significantly increased plasma HDL by 18.8% and 14.3% respectively (P<0.001), decreased triglyceride by 38.2% and 37.2% (P<0.001), but with no significant change in LDL levels. Furthermore, we observed a decreasedin total cholesterol levels compare to baseline by 8.4%(P<0.05)and 3.1% (P=0.114), intotal cholesterol/HDL ratio by17.6% and 18.4% (P<0.001), in fibrinogen level by 13.8% and 6.4% and an increase in ApoA-1 by 15.0% and 9.7%for lipanthyl and trichol, respectively. Interestingly, the decrease in total cholesterol level is significantly higher in trichol than lipanthyl groups (P<0.05).The adverse events of both treatments were comparable.The lipid-modifying effects of 300 mg daily dose of trichol is comparable to that of 160 mg daily dose of lipanthyl. Both drugs efficiently increased the plasma HDL levels and decreased plasma triglycerides concentration. Besides, a significant reduction of total cholesterol was achieved after 12 weeks treatment with trichol, but not lipanthyl. (Med J Indones 2007; 16:159-67)